Venography of intrahepatic portal veins of the liver in buffalo (Bubalus bubalis) - ANURADHA, ANURADHA; SINGH, OPINDER (The Indian Journal of Animal Sciences, 2014)
The radiological examination of intrahepatic portal vein was conducted in the liver obtained from tixed carcasses 01'6apparently healthy bufTalo calves. The venograms and dissection revealed that the portal vein divided at porta into right and left interlobar veins. The right one was smaller and left one was longer. Right interlobar again guve dorsal, intermediate and ventral interlobular veins. Dorsal supplied dorsal and ventral supplied ventral part of right lobe of liver and intermediate vein supplied quadrate and caudate lobe. The left interlobar vein had transverse and urnblieal parts. Transverse part supplied caudate lobe and umblical interlobar gave dorsal, intermediate and ventral interlobular veins supplying dorsal, ventral part of left lobe and quadrate lobe. Each interlobular vein again gave 3 to 5 small branches (intralobular veins) to the liver parenchyma.